Pengaruh Sari Kacang Ijo Dan Tablet Fe Terhadap Peningkatan Kadar Hb Ibu Hamil dengan Anemia - Misrawati Misra; Marliah Marliah (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2019)
This study aims to determine the effect of green bean extract and fe tablets on increasing Hb levels in anemic pregnant women at Bara Baraya Makassar Health Center in 2018. The type of research Quasi Experimental Design is research conducted by giving experiments or treatments. This study used the Nonequivalent Control Group Design design, namely the intervention group (pregnant women who were given green beans and Fe tablets) and control groups (pregnant women who consumed Fe tablets). The population is all pregnant women who visited on April 9 - June 9 at the Bara Baraya Health Center Makassar in 2018, amounting to 200 pregnant women, while the sample in this study were 30 respondents with sampling using the proposive sampling technique. From the results of this study, the value of data analysis was obtained by using Wilcoxon test and Mann Whitney test. There was an effect of green bean juice and fe tablet on increasing Hb levels in anemia pregnant women where the value of ρ = 0.00 <α = 0.05 and sig value or value of , 002 <α = 0.05. which means Ho is rejected and Ha is accepted.